2020
DOI: 10.4236/jss.2020.811018
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Instructional Design and Instructional Material on Learners’ Motivation and Completion Rates of a MOOC Course

Abstract: Despite the formal, non-formal and informal training opportunities offered by MOOCs, they show low completion rates due to both personal factors of the participants and the instructional design of the courses. Empirical research has shown that good instructional design can help increase learners' motivation, helping them achieve high performance by completing the program. To determine to which extent the quality instructional material, which is the result of a good instructional design, contributes to their mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…There is also a feature to correct the mistake we made in that application, so it is helpful to design it well before publishing. However, the instructional design will influence learners' motivation (Giasiranis & Sofos, 2020). Using Telegram to deliver learning material, lecturers will use writing most of the time.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a feature to correct the mistake we made in that application, so it is helpful to design it well before publishing. However, the instructional design will influence learners' motivation (Giasiranis & Sofos, 2020). Using Telegram to deliver learning material, lecturers will use writing most of the time.…”
Section: Discussionmentioning
confidence: 99%
“…A satisfação do aluno em cursos na modalidade EaD pode ser influenciada por fatores como o conteúdo oferecido, design instrucional e motivação pessoal para aprimoramento profissional (GIASIRANIS;SOFOS, 2020;DINH et al, 2022). Ter mais experiência em cursos on-line ou com computadores/notebooks também influenciam a satisfação, por possibilitar familiaridade e conforto ao utilizar tecnologias digitais, possibilitando maior engajamento no aprendizado (MOURÃO; ABBAD; ZERBINI, 2014).…”
Section: Discussionunclassified
“…Chang et al (2016) in their research also have adapted and integrated ARCS features in the learning material, and they have found that their respondents' motivation level when learning foreign language via mobile learning approach shows an increase especially in terms of Relevance, Confidence, and Satisfaction dimensions compared to students who are not exposed to the ARCS characteristics. Therefore, if motivation considerations such as attention, relevance and confidence become the priority and are incorporated in the learning activities, learners are expected to enjoy the learning and satisfy over all their learning experiences (Giasiranis & Sofos, 2020).…”
Section: Background Of Studymentioning
confidence: 99%
“…Next consideration is Relevance. The relevancy to what each learner is learning is important to be revealed; for example -their learning goals, needs and expectations (Giasiranis & Sofos, 2020). Learners are able to foresee their learning target clearly which helps them continue learning.…”
Section: Keller's Arcs Motivation Modelmentioning
confidence: 99%